The Effect of Company Image on Satisfaction and Customer Loyalty in Insurance Jiwasraya in City of Makassar - Hafipah Hafipah; H. Mahfudnurnajamuddin H. Mahfudnurnajamuddin; H.Sabri Hasan; Ilham Labbase (Journal of International Conference Proceedings (JICP), 2018)
This study aims to analyze the effect of corporate image on customer satisfaction, the influence of company image on customer loyalty, the effect of satisfaction on customer loyalty at PT. BNI Life Insurance in the city of Makassar. Data collection through questionnaires using SEM analysis methods. The population is customers registered in 2017 as many as 1,537 people. The sample is 230 customers. The results of this study found that empirically the company's image has a positive and significant effect on customer satisfaction, the company's image has a negative and not significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty. Keywords: Corporate image, satisfaction and loyalty